Răspuns :
a = 3b b = 2c a - b = 40
a =3·2c = 6c 6c - 2c = 40 4c = 40 c = 10 b = 20 a = 60
3a - 4b + 5c = 3·60 - 4·20 + 5·10 = 150
a =3·2c = 6c 6c - 2c = 40 4c = 40 c = 10 b = 20 a = 60
3a - 4b + 5c = 3·60 - 4·20 + 5·10 = 150
a:b=3⇒ a =3b
b:2=c⇒ b = 2c
a - b = 40
a =3·2c = 6c 6c - 2c = 40 4c = 40 c = 10
b = 2c = 20 a = 3b= 3×20= 60
a=60; b=20, c=10
3a - 4b + 5c = 3×60 - 4×20 + 5×10 = 150
3a - 4b + 5c = 150
b:2=c⇒ b = 2c
a - b = 40
a =3·2c = 6c 6c - 2c = 40 4c = 40 c = 10
b = 2c = 20 a = 3b= 3×20= 60
a=60; b=20, c=10
3a - 4b + 5c = 3×60 - 4×20 + 5×10 = 150
3a - 4b + 5c = 150